High-resolution magnetic resonance vessel wall imaging in extracranial cervical artery dissection - Shao, Sai; Wang, Guangbin (Frontiers in Neurology, 2025)
Extracranial cervical artery dissection (eCAD) is the second leading cause of stroke in young and middle-aged adults. Clinical management strategies for eCAD are continuously being explored and optimized, as revealed by the recently published CADISS and TREAT-CAD studies. The type of drug, dosage, and timing of administration can affect the regression of carotid artery dissection and the risk of recurrence of stroke. Based on imaging evidence, it is important to develop individualized treatment strategies for different risk groups. Currently, High-resolution magnetic resonance vessel wall imaging (MR-VWI) technology has made significant progress in the qualitative diagnosis of eCAD, vascular lesion progression, and the assessment of recurring ischemic stroke risk. To better understand the pathogenesis and progression of eCAD using MR-VWI, a comprehensive review is presented here.